Sosialisasi Pengenalan Siklus Aedes aegypti untuk Meningkatkan Kesadaran Pencegahan Demam Berdarah Dengue pada Siswa SDN 1 Sungai Besar Banjarbaru - Muhamat Muhamat; Abdul Gafur; Rakmawati Rakmawati; Lucia Desti Anitasari; Hameda Dhaka Kusuma Taufiq; Hikmah Maulidiyah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The Aedes aegypti mosquito is a vector for transmitting the dengue virus, which causes dengue hemorrhagic fever (DHF). This community service program was carried out by providing outreach and mentoring regarding the bioecology of Ae. aegypti to students of SDN 1 Sungai Besar, Banjarbaru. The limited knowledge of the school community, especially the students of SDN 1 Sungai Besar, about vector mosquitoes and their bioecology makes them less concerned about the environment. Systematic knowledge about DHF must be implemented from an early age to help raise awareness of the importance of sanitation in preventing the home and school environment from becoming mosquito habitats. Pre-test and post-test questionnaires were used to measure students' understanding of the bioecology of Ae. aegypti mosquitoes and were given to 25 students. Based on data analysis, it can be concluded that the outreach and mentoring program is effective and can help increase students' knowledge of the importance of sanitation in preventing the home and school environment from becoming mosquito habitats. This activity needs to be carried out in schools in Banjarbaru City so that the school environment does not become a habitat for Ae. aegypti mosquitoes.